The Mundell-Fleming Trilemma Combination on Middle-Income Countries - Rinny Apriliany Zakaria; Ghozali Maski; Putu Mahardika Adi Saputra; Ahmed Mohamed Annegrat (Universitas Negeri Malang, 2023)
The Mundell-Fleming trilemma hypothesis stated that a country could not simultaneously achieve exchange rate stability, financial integration, and monetary independence. The fixed exchange rate policy, free capital mobility, and monetary independence are trade-offs and impossible to run simultaneously. This research aims to identify the combination of the Mundell-Fleming trilemma formed in middle-income countries. Using the panel ARDL model, we found that the Mundell-Fleming trilemma tends to converge in the short run. While on the long run, middle-income countries tend to choose monetary independence and financial integration, resulting in a less stable exchange rate, as mentioned in the hypothesis